Fano resonances in a plasmonic waveguide system composed of stub coupled with a square cavity resonator. (14th March 2016) - Binfeng, Yun; Hu, Guohua; Zhang, Ruohu; Yiping, Cui
Abstract: A coupled plasmonic waveguide resonator system which can produce sharp and asymmetric Fano resonances was proposed and analyzed. Two Fano resonances are induced by the interactions between the narrow discrete whispering gallery modes in a plasmonic square cavity resonator and the broad spectrum of the metal–insulator–metal stub resonator. The relative peak amplitudes between the 1st and 2nd order Fano resonances can be adjusted by changing the structure parameters, such as the square cavity size, the stub size and the center-to-center distance between the square cavity and the stub resonators. And the 1st order Fano resonant peak, which is a standing-wave mode, will split into two resonant peaks (one standing-wave mode and one traveling-wave mode) when it couples with the 2nd Fano resonance. Also, the potential of the proposed Fano system as an integrated slow-light device and refractive index sensor was investigated. The results show that a maximum group index of about 100 can be realized, and a linear refractive index sensitivity of 938 nm/RIU with a figure of merit of about 1.35 × 10 4 can be obtained.